A Nutraceutical Composition Decreases CPK Levels in Saos-2 Cells and in Patients with Elevated Serum Levels of This Enzyme. (17th August 2016) - Ammendola, Sergio; Stoppoloni, Daniela; Loreto, Mario Di; d'Abusco, Anna Scotto
Abstract : Objectives : This study aimed to investigate the effects of a nutraceutical composition on the expression of some genes involved in muscle cells and functioning in osteoblast cells. The effects of nutraceutical composition have been compared to the effects of atorvastatin, which induces muscle pain and elevated creatine phosphokinase (CPK) serum level when administered to patients. In particular, we analyzed the MyoD-1 gene, which is responsible for modulation of the CPK gene, which is a marker of muscle pain and damage. Methods : The effects of nutraceutical composition on Saos-2 cells were compared with the effects of atorvastatin. The mRNAs were extracted and the expression levels of mitochondrial and cytoplasmic CPK genes and MyoD - 1 were analyzed by real-time polymerase chain reaction (RT-PCR). Moreover, the effects on lactate dehydrogenase (LDH) activity and adenosine triphosphate (ATP) synthesis were measured in the osteoblast cell line. Furthermore, 11 patients with muscle pain or elevated CPK serum levels received a supplementation of the nutraceutical composition to test whether CPK levels could be downregulated. Results : The analysis in Saos-2 cells showed that the nutraceutical composition upregulates the gene expression of MyoD-1 and downregulates the expression of the cytoplasmic isoform of CPK gene expression ( p ≤ 0.05); moreover, it slightly increases ATP amount and decreases LDH activity. Conversely, atorvastatin represses the expression of MyoD-1 gene without significant changing into the expression levels of both cytoplasmic and mitochondrial CPK genes. Moreover, atorvastatin does not increase the ATP amount or increase LDH activity. Remarkable, the nutraceutical composition is able to decrease CPK levels in serum of patients and in some cases improve myalgia symptoms. Conclusion : The nutraceutical composition decreases CPK levels both in vitro and in vivo, suggesting that it might be useful to management of nonneurological myalgia symptoms.